Self-Compassion from a Cultural Perspective: A Comparative Study of the Minahasa and Sundanese Ethnic Groups - Nabilah, Najla Fauziyyah Alma; Fitriah, Elis Anisah (Jurnal Psikologi Islam dan Budaya, 2025)
The level of an individual's self-compassion is shaped by their social environment and the cultural background in which they live. This study aims to examine the differences in self-compassion levels between individuals from the Minahasa and Sundanese ethnic groups, as well as to explore the moral and ethical values underlying self-compassion within each cultural context. A mixed-methods approach was employed, combining quantitative analysis using self compassion scale and qualitative data gathered through open questionnaire. The quantitative findings revealed a significant difference between the two groups (p = 0.002), with individuals from the Minahasa ethnic group demonstrating higher levels of self-compassion compared to those from the Sundanese group. Qualitative results indicated that while moral and ethical values serve as the foundation of self-compassion for both groups, these values are interpreted differently according to their respective cultural frameworks. These findings highlight the importance of considering cultural context in understanding and fostering self-compassion as a crucial aspect of individual mental health.